PUBLIC ATTENTION'S EFFECT ON LOCAL GOVERNMENT PERFORMANCE ACCOUNTABILITY IN INDONESIA - Agung Dwi Mahendra; Payamta Payamta (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research examines the accountability of local government performance. The objective of this study is to obtain empirical evidence regarding the influence of public attention on the accountability of local government performance in Indonesia. The sample used in this research consists of 1,542 local governments in Indonesia in 2018 and 2020. The variables employed include the dependent variable, which is the accountability of local government performance; the independent variable, public attention proxied by internet search activity; and control variables such as government size, complexity of local government, region type, and geographic location of the local government. This study utilizes secondary data obtained from the Financial Statements of Local Governments (LKPD), the Annual Reports of the Ombudsman, the Ministry of Administrative and Bureaucratic Reform (PAN and RB), and data from the Central Bureau of Statistics (BPS). The research findings indicate that independent variables, namely internet search activity, have a positive influence on the accountability of local government performance. Furthermore, the control variables of government size and geographic location of the local government have an impact on the accountability of local government performance, while the complexity and type of local government do not affect the accountability of local government performance.